REAL-T: Time Modularization in Reactive Distributed Applications (2018)
In this paper, we propose REAL-T, a distributed event-based language with explicit support for time manipulation. The language introduces automata for operational time manipulation, causality constructs and Linear Temporal Logic for declarative time predicates, and a distributed-time aware event model. We have developed a compiler for the language and a dynamic run-time framework. To validate the proposal we study detection of complex patterns of security vulnerabilities in IoT scenarios.